Study and evaluation of economical and hygienic effects of aflatoxin B1 in cultured Huso huso - Sepahdari, Abolfazl; Mohseni, M.; Pourali, H.R.; Ghiasi, M.; Hallajian, A.; Shenavar Massoleh, A.R.; Pourdehghani, H.; Gholamipour, S.; Kakoolaki, S.; Masoumzadeh, M.; Binaei, M. (Iranian Fisheries Science Research Institute, 2011)
In the present study, the impacts of various concentrations of Aflatoxin B1 (AFB1) on Beluga, Huso huso, under controlled conditions were investigated. Belugas (120±10 g) were fed diets containing 0, 25, 50, 75, and 100 ppb AFB1/kg of diet for 3 months. Results showed that various levels of AFB1 do not significantly affect the specific growth ratio (SGR) (p< 0.05) of fish in different treatments. However, weight gain and food conversion ratio (FCR) varied significantly (p< 0.05 between control and treatments with diets contaminated with 75 and 100ppb AFB1/kg after 90 days). The increase in level of AFB1 did not affect the percent of survival rate (SR) and no mortality was observed in treatments (SR=100%). Various levels of AFB1 under experimental conditions of the present study affect some growth factors, such as, weight gain and FCR but have no significant impact on SGR. Histopathological studies showed that different level of AFB1 can cause broad range of changes in liver, kidney, spleen and gills tissues, particularly at concentration of 75 and 100 ppb AFB1/kg of diets after 60 days. No tumor formation observed. With regard to toxin concentration and time of exposure to AFB1 in experimental fish, different degree of skin lesions (simple hemorrhage to progressive wounds) were observed in different parts of body especially in vent, caudal peduncle, fins, and head. "Yellow sores" on head and trunk regions are considerable and led to deterioration of appearance. Prevalence of skin lesion in different treatments was 8 -53.3 %, which after stop feeding with toxic diets, 16-24 % healing observed. Haematological changes included chronic anemia and lymphocyteopenia. Also neutrophilia observed with increasing of skin lesions. Meat accumulation of AFB1 in different treatments is not so considerable and harmful for human consumption, but is significantly different with control fishes (P<0.01).